Opportunities for renewable energy in large Saskatchewan irrigation projects evaluated in HOMER pro software - David Ross-Hopley; Ryan Husband; Lord Ugwu; Hussameldin Ibrahim (Sustainable Chemistry for Climate Action)
With a less predictable climate, irrigated agriculture may contribute to global food security. Irrigation requires large water and energy inputs – creating a water-food-energy nexus. In Saskatchewan, irrigation typically sources energy from the provincial electrical utility, SaskPower. Using current utility infrastructure, dependence deepens the use of conventional fossil fuel power. With major cost decreases, renewable energy alternatives are increasingly techno-economically competitive. In undertaking energy system modelling using HOMER Pro software, this study investigates the viability of renewable energy for irrigation projects in Saskatchewan. Modelling includes a conventional energization scenario (energy provision through grid interconnection), a combination of conventional and renewable scenario, as well as a 100 % renewable scenario. Further, sensitivity analysis has been undertaken for permitted capacity shortages, utility rates, grid interaction and carbon pricing. The study provides the levelized cost of electricity for each scenario. Baseline results range from $0.0154/kWh for optimised hybrid systems, $0.1429/kWh for grid systems, and as high as $1.1101/kWh 100 % renewable energy systems. The success of renewable energy-driven integration is closely linked to the presence of a grid connection, and the rates governing interactions.